Pengelolaan Pemberdayaan Ekonomi pada Pesantren Salaf dan Modern di Temanggung - Syafi', Moh (Jurnal Pemberdayaan Masyarakat, 2023)
Apart from being an institution that functions to carry out education, Islamic boarding schools also function as institutions that develop their functions in community empowerment. This is because pesantren cannot be separated from the emergence of pesantren as Islamic educational institutions born by, from and for the community, so that their existence is inherent in the surrounding community. Thus, pesantren are required to be open and responsive to wider societal problems, especially in the economic field. This is because Islamic boarding schools as a specialty of Islamic education in Indonesia were born and developed based on the awareness of social inclusion around them. therefore at least pesantren can do reciprocity through empowering the community's economy. What is the function of empowerment in salaf and modern pesantren in Temanggung, especially in the economic field, it is interesting to study, considering that the function of empowerment is an important aspect in both salaf and modern pesantren. The purpose of this study is to see how the functions and forms of management of community empowerment in salaf and modern Islamic boarding schools are so that they get representation in the respective types of Islamic boarding schools in Temanggung. By using a phenomenological approach, that salaf and modern pesantren have carried out the function of empowering their students with a directed democratic leadership pattern. A kiai in these two pesantren gives freedom to the santri to manage business in the economic sector but with participatory supervision and guidance from a kiai. However, on the other hand, the function of empowerment in these two Islamic boarding schools has not involved the community around the pesantren in a participatory way. The community is more empowered not to become an integral part of management, but only as partners in the pesantren's economic business